Time to exhaustion at intermittent maximal lactate steady state is longer than continuous cycling exercise - Grossl, T.; Dantas de Lucas, R.; Mendes de Souza, K.; Antonacci Guglielmo, L. G. (Applied Physiology, Nutrition, and Metabolism, 2012)
The maximal lactate steady state (MLSS) represents a submaximal intensity that may be important in prescribing both continuous and interval endurance training. This study compared time to exhaustion (TTE) at MLSS in continuous and intermittent (i.e., with pauses) exercise, investigating whether physiological variables differ between these exercise modes. Fourteen trained male cyclists volunteered for this investigation and performed an incremental test, several 30-min tests to determine two MLSS intensities (continuous and discontinuous protocol), and two randomized tests until exhaustion at MLSS intensities on a cycle ergometer. The intermittent or discontinuous protocol was performed using 5 min of cycling, with an interval of 1 min of passive rest. TTE at intermittent MLSS was 24% longer than TTE at continuous exercise (67.8 ± 14.3 min vs. 54.7 ± 10.9 min; p < 0.05; effect sizes = 1.04), even though the absolute power output of intermittent MLSS was higher than continuous (268 ± 29 W vs. 251 ± 29 W; p < 0.05). Additionally, the total mechanical work done was significantly lower at continuous exercise than at intermittent exercise. Likewise, regarding cardiorespiratory and metabolic variables, we observed greater responses during intermittent exercise than during continuous exercise at MLSS. Thus, for endurance training prescription, this is an important finding to apply in extensive interval sessions at MLSS. This result suggests that interval sessions at discontinuous MLSS should be used instead of continuous MLSS, as discontinuous MLSS allows for a larger amount of total work during the exhaustion trial.